Phase stability in the Cu-9 wt%Al-10 wt%Mn-3 wt%Ag alloy - Santos, C. M. A. [UNESP]; Adorno, A. T. [UNESP]; Paganotti, A.; Silva, C. C. S.; Oliveira, A. B.; Silva, R. A. G. [UNESP] (Elsevier B.V., 2017)
The phase stability in the Cu-9 wt%Al-10 wt%Mn-3 wt%Ag alloy was analyzed using differential scanning calorimetry (DSC), X-ray diffractometry (XRD), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), optical microscopy (OM) and microhardness measurements with quenching temperature. The results showed that the presence of silver alters the phase stability range and enhances the effect of bainite precipitation on the microhardness values of the Cu-9 wt%Al-10 wt%Mn-3 wt%Ag alloy.
Keywords: Cu-based alloys; Phase stability; Bainitic precipitation